Web-Based Application for New Student Admissions (PPDB) at SMP Negeri 1 Ledo - Yogie Meirian; Heri Priyanto; Morteza Muthahhari (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this study the model used is the waterfall model in designing and building new student admissions information systems, the waterfall model is a model that is part of the System Development Life Cycle (SDLC) design model, where the design begins with the process of requirements, design, implementation, integration & testing, operations & maintenance. Data collection techniques through field observations, interviews, and literature studies. The new student admission application is designed based on a website using the PHP programming language with a MySQL database, and SublimeText3 as an editor. This application has two levels of access rights, namely admin, and prospective students. Admin has the highest access rights and can perform user management, form data for prospective students, as well as management of the number of prospective students who have passed, and prospective students have the lowest access rights in the application. The purpose of making this research is to develop new student acceptance applications that are able to manage the implementation of new student admissions. Applications for accepting new students can help admins and prospective students in accepting new students so that PPDB can run more effectively and efficiently. The result of making this final project is a Website-Based New Student Acceptance Application at SMP Negeri 1 Ledo.